(E)-1-[(2,4,6-Tribromophenyl)diazenyl]naphthalen-2-ol - Chetioui, Souheyla (International Union of Crystallography, 2013)
The title azo molecule, C(16)H(9)Br(3)N(2)O, adopts a trans conformation with respect to the azo N=N double bond. An intramolecular O—H⋯N hydrogen bond forms an S(6) ring motif. The dihedral angle between the naphthalene ring system and the benzene ring is 33.80 (16)°. In the crystal, molecules are stacked in columns along the a axis by π–π interactions [centroid–centroid distances = 3.815 (3) and 3.990 (3) Å].